Prevalência e fatores associados à polifarmácia entre idosos atendidos na Atenção Primária a Saúde em Belo Horizonte, MG. - Patricia Carvalho de Oliveira (2018)
The progressive aging of the population contributes to an increase in the number of people who develop chronic health conditions, which in general require continuous care and the use of various medicines. The age-related physiological changes associated with the high burden of chronic diseases in the population and the high consumption of multiple medications make the elderly more vulnerable to drug-related problems and, consequently, to negative health outcomes. In view of the above and considering the importance of Primary Health Care (PHC) in health promotion and in the prevention of diseases, it was necessary to evaluate the existence and distribution of polypharmacy (concomitant use of five or more drugs) and polypharmacy excessive use (concomitant use of ten or more drugs) in part of the elderly attending this level of care. The objectives of this study were to analyze the prevalence of polypharmacy and excessive polypharmacy, as well as its associated factors, between the elderly attended at two Basic Health Units (BHU) of Belo Horizonte (MG) between 2013 and 2014. A cross-sectional study was conducted through a structured interview with the patient. The sample consisted of 227 elderly people who received at least one medication in the UBS pharmacies. We analyzed the individual associations of each explanatory variable with polypharmacy and with excessive polypharmacy. For the variables that showed a significant association with polypharmacy, a multivariate analysis was performed using the logistic regression model. The elderly used an average of 5.2 drugs (SD = 2.3), and the use of up to 13 drugs simultaneously was observed. The prevalence of polypharmacy was 57.7% and excessive polypharmacy was 4.8%. They were individually associated with polypharmacy, increasing their prevalence, the conditions: age 70 years, schooling> 8 years, presence of more than three diseases and presenting symptoms of depression. For excessive polypharmacy, the following conditions were associated with increased prevalence: presence of more than three diseases, self-perception of negative health, and partial dependence on instrumental activities of daily living. In the final multivariate model for polypharmacy, the variables age 70 years (RC: 1.93, 95% CI: 0.98-3.81) and presence of more than three diseases remained (RC: 4.24; %: 2.39-7.51). The multivariate regression model for excessive polypharmacy could not be adjusted because of the low number of observations of the event. The prevalence of polypharmacy was high among the elderly attended at the two basic healthcare units of the SUS. The factors age less than or equal to 70 years and the presence of more than three diseases were positively associated with the use of five or more drugs. These findings are of great relevance in the sense of encouraging and guiding public health policies related to the use of drugs by the elderly.